Policy Networks in Ecotourism Governance: Evidence from Local Perspective - Tamrin, M. Husni; Roziqin, Ali (Technium Social Sciences Journal, 2024)
This study examined the governance of ecotourism at Dalegan Beach, with a focus on policy networks. The goal is to provide insights concerning actor, role, functions, characteristic, power relations and strategies, as well as factors driving and inhibiting the formation of network. The qualitative method was used to collect data through observations, in-depth interviews with informants, and document studies. The findings showed that the participation and roles of stakeholders, ranging from provincial governments to local communities, had a significant impact on beach tourism management. Despite the establishment of policy networks, challenges such as membership instability and coordination limitations among stakeholders linger. The concept of policy networks as a dynamic interaction system underscores the evolving relationships among various actors in the policy environment. These interactions are influenced by factors such as interests, preferences, and power dynamics among actors, which are used to influence decision-making processes and policy outcomes. The strategies employed by each actor can affect network dynamics and the policy process outcomes. Therefore, changes in the structure or power relations among actors in policy networks can impact the shape and direction of the policies.